2016
DOI: 10.1038/npjquantmats.2016.12
|View full text |Cite
|
Sign up to set email alerts
|

Switchable electric polarization and ferroelectric domains in a metal-organic-framework

Abstract: Multiferroics and magnetoelectrics with coexisting and coupled multiple ferroic orders are materials promising new technological\ud advances. While most studies have focused on single-phase or heterostructures of inorganic materials, a new class of materials\ud called metal–organic frameworks (MOFs) has been recently proposed as candidate materials demonstrating interesting new routes\ud for multiferroism and magnetoelectric coupling. Herein, we report on the origin of multiferroicity of (CH3)2NH2Mn(HCOO)3 via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
96
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(98 citation statements)
references
References 43 publications
2
96
0
Order By: Relevance
“…16 This dovetails with a recent report of sizable magnetoelectric coupling at elevated temperatures. 21 These findings suggest that there may be a magnetically-driven transition at higher fields -beyond the phase space that has been thus far explored. 18,22 Other perovskite-like materials including the rare earth manganites also sport exotic phase diagrams, 23 providing additional motivation for measurements of [(CH 3 ) 2 NH 2 ]Mn(HCOO) 3 under external stimuli.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…16 This dovetails with a recent report of sizable magnetoelectric coupling at elevated temperatures. 21 These findings suggest that there may be a magnetically-driven transition at higher fields -beyond the phase space that has been thus far explored. 18,22 Other perovskite-like materials including the rare earth manganites also sport exotic phase diagrams, 23 providing additional motivation for measurements of [(CH 3 ) 2 NH 2 ]Mn(HCOO) 3 under external stimuli.…”
Section: Introductionmentioning
confidence: 83%
“…At the same time, fits to the susceptibility in the vicinity of the ferroelectric transition, 16 our magnetization data above T N which extends to 12 K (Fig. 4), and the sizable magnetoelectric coupling at elevated temperatures (up to 40 K) 21 indicate that short range interactions are important, although the temperature range is more limited. Nuclear magnetic resonance measurements on the Zn analog, on the other hand, reveal that T C itself is insensitive to magnetic field and that there is no ordering of the amine -at least up to 5 T. 44 That spin resides on the metal-organic framework is consistent with our spin density calculations in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that compounds with Mn exhibit strong d-π hybridization, which leads to partially filled low-spin levels, in contrast to compounds with transition metals, for which the Fermi energy is weakly split by spin due to weak d-π hybridization and magnetic interaction. In this case, the 3D MOF, (CH 3 ) 2 NH 2 Mn(HCOO) 3 , exhibits a perovskite architecture with ferroelectric domains, the magnetic states of which can be controlled by an electric field at temperatures below 180 K. [93] At present, structures with reversible/nonreversible phasechange effects are applied for triggers, switchers and other active elements for optical, magnetic, and microelectronic devices. [62] In the case of chained MOFs such as NU-901, one can observe electrochromic switching between yellow and deep blue hues by applied potential, due to a single-electron redox reaction on their pyrene-based linkers.…”
Section: Phase-change Effectmentioning
confidence: 99%
“…Metal organic framework (MOF) materials having ABX 3 perovskite structure, where A is the dimethyl ammonium cation (DMA + ; DMA cation), B = Mn, and X is HCOO − formate ion, are known to exhibit multiferroic properties with an electrical ordering between 180 and 190 K and magnetic ordering at still lower temperature (8–10 K) . At room temperature, this compound crystallizes in the trigonal space group R3̅c, where the DMA cations in the perovskite‐like cages are orientationally disordered.…”
Section: Introductionmentioning
confidence: 99%
“…This orientational ordering is related to the freezing of the internal rotation of DMA + ion with respect to the C–C axis of DMA cation, induced by hydrogen‐bond formation between the nitrogen atoms of the DMA + ions and the oxygen atoms of the formate frameworks, as shown in Figure S1b. The nature of this ferroelectric transition has been probed using several techniques such as electrical polarization, crystallographic methods, neutron scattering, dielectric measurements, thermal, magnetic, and electron paramagnetic resonance (EPR) methods . Optical techniques sensitive to local structural changes such as infrared (IR) and Raman spectroscopy have been carried out on DMMn to investigate the actual microstructural mechanism involved .…”
Section: Introductionmentioning
confidence: 99%